The challenges faced by single mothers in Malaysia during the COVID-19 pandemic - Mohamad Nawawy, Jusoh; Fatmawati, Latada (Kolej Universiti Islam Pahang Sultan Ahmad Shah (KIPSAS), 2020)
Coronavirus is a type of virus that infects humans, leading to an upper respiratory infection or death. The transmission of the coronavirus disease (Covid-19) has caused great distress in many countries, including Malaysia. This study aims to underline the challenges of single mothers during the Covid-19 pandemic. This paper will look into three main challenges; single mothers’ emotional and psychological state in maintaining the balance between working caring, educating and disciplining their children, their financial distress, as well as additional roles and responsibilities forced upon single mothers during this pandemic. Single mothers are women with children under age 18 headed by a parent who is widowed or divorced and not remarried, or by a parent who has never married. Life as a single mother is associated with high demands and challenges. Social routines that many single mothers rely on to provide stability to their daily lives such as work schedules, sending children to day care or schools, visiting friends and families, are no longer possible as the entire country was put on the Movement Control Orders (MCO), three subsequent MCOs and social distancing requirements. The MCO was implemented in Malaysia to stop the spread of the Coronavirus. This study uses the library research methodology which includes the process of identifying relevant information and analysing other studies from primary sources (government documents and surveys) as well as secondary sources (books, journals, articles, etc.). The researcher was able to develop and express ideas on the issue above. Outcomes demonstrate that single mothers in Malaysia face many challenges, including the difficulty to maintain a sense of authority in their new norm; the struggle to keep food on the table; and the loss of the social support during the Covid-19 Movement Control Order. Single mothers in Malaysia take up so many challenges, roles and burden in bringing up the country’s future generation. More assistance and aid should be provided to single mothers in the country to ensure mothers’ physical and emotional well-being It is hoped that the discussion in this paper will be an eye opener to readers that single mothers should also be considered the country’s ‘front liners’ and unrecognized heroes.